Pengaruh Political Organization, Organizal Climate, dan Organizational Culture terhadap Organizational Citizenship Behaviour (OCB) dengan Job Satisfaction sebagai Variabel Intervening - Usman, Sherlyta (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2026)
This study aims to examine and analyze the political organization, organizational climate and organizational culture with organizational citizenship behavior (OCB) and job satisfaction as an intervening variable for employees of PT. Allianz Life Indonesia. The object of this research is 100 employees of PT. Allianz Life Indonesia. The approach used in this research is Component or Variance Based Structural Equation Model with analysis tool Smart-PLS. The results showed Political organizationa that has positive significant effect on job satisfaction. Organizational climate that has positive significant effect on job satisfaction pada karyawan PT. Allianz Life Indonesia. Organizational culture that has positive significant effect on job satisfaction. Political organization does not affect organizational citizenship behavior (OCB). Organizational climate that has positive significant effect on organizational citizenship behavior (OCB). Organizational culture that has positive significant effect on organizational citizenship behavior (OCB). Job satisfaction that has positive significant effect on organizational citizenship behavior (OCB).